1998
DOI: 10.1007/bf03012025
|View full text |Cite
|
Sign up to set email alerts
|

The use of glycopyrrolate in a case of intermediate syndrome following acute organophosphate poisoning

Abstract: The use of glycopyrrolate in a case of intermediate syndrome following acute organophosphate poisoningPurpose: This report describes a case of organophosphate intoxication refractory to atropine in which glycopyrrolate was used to reduce cholinergic symptoms, and describes the development of intermediate syndrome, an uncommon subacute complication of organophosphate poisoning. Clinical features: A 44-yr-old woman presented in cholinergic crisis following malathion ingestion. Treatment was initiated with atropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Although atropine injection remains the standard treatment for acute OP poisoning, other anticholinergic agents have also been suggested and used in this setting. Bardin and Eeden 11 found that glycopyrrolate-a highly polar quaternary ammonium compound that does not cross the blood-brain barrier, [11][12][13] was equally effective in treating OP poisoning when compared with atropine, in patients who survived to hospital arrival. Ipratropium bromide (also a quaternary ammonium chemical) has also been used effectively in the setting of acute OP poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Although atropine injection remains the standard treatment for acute OP poisoning, other anticholinergic agents have also been suggested and used in this setting. Bardin and Eeden 11 found that glycopyrrolate-a highly polar quaternary ammonium compound that does not cross the blood-brain barrier, [11][12][13] was equally effective in treating OP poisoning when compared with atropine, in patients who survived to hospital arrival. Ipratropium bromide (also a quaternary ammonium chemical) has also been used effectively in the setting of acute OP poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Despite limited evidence, glycopyrrolate is not inferior to atropine, and should be considered an appropriate alternative to atropine if atropine supply is limited. 86 Finally, if bronchorrhea and bronchoconstriction are the primary forms of toxicity, ipratropium can be administered by inhalation with direct effects on the target end organ. 87,88 Indications for antimuscarinic pharmacologic therapy are provided in Table 4.…”
Section: Glycopyrrolatementioning
confidence: 99%
“…It has been shown that a smaller than traditional dose of atropine used over a shorter duration at a hospital in China was associated with lower complication and mortality rates [131]. A case of OP poisoning refractory to atropine, and in which glycopyrrolate was used to reduce cholinergic symptoms, was reported recently [9].…”
Section: Atropine or Glycopyrrolatementioning
confidence: 99%
“…Organophosphorusbased pesticides are widely used globally and have emerged as the major pesticide contributor to ill health [2]. Ill health related to these irreversible inhibitors of acetylcholinesterase has been reported recently in studies from China [3], India [4][5][6], Brazil [7], Mexico [8], Canada [9], Costa Rica [10], Columbia [11], Puerto Rico [12], France [13], Spain [14,15], Poland [16], Italy [17,18], Belgium [19], Romania [20], Portugal [21], Greece [22], Germany [23], Japan [24], Jordan [25], South Africa [26], Turkey [27], Taiwan [28] and Sri Lanka [29,30]. In 1996, the American Association of Poison Control Centers reported 86 914 human exposures to pesticides in the US [31].…”
mentioning
confidence: 99%